Renteng Dance in Saren Village, Nusa Penida as a Source of Inspiration for the Creation of Ceremonial Dances in Bali - Ruastiti, Ni Made; Indrawan, Anak Agung; Sariada, I Ketut (Harmonia: Journal of Arts Research and Education, 2021)
This article aims to discuss the Renteng Dance in Saren Village, Nusa Penida, which is actually the forerunner of the Rejang Renteng Dance performance, which is now widely danced by mothers in the context of the dewa yadnya ceremony in Bali. Supposedly, as the forerunner of ceremonial dance performances, the Balinese people know the Renteng Dance. However, in reality, this is not the case. Balinese people seem to know more about the Rejang Renteng Dance than the Renteng Dance. (1) What is the form of the Renteng Dance in Saren Village? (2) Why is the Renteng Dance the source of the creation of ceremonial dance in Bali? This study uses a qualitative method with research data sources such as Renteng Dance performances, dancers, musicians, traditional elders, community leaders, and journals related to research results. Aesthetic theory and structural-functional theory were used to analyze all the data gathered during the observation, interviews, and literature review. The study results show that: (1) the community in Saren Village presents Renteng Dance in the form of a freelance dance (without a play). It can be seen from the way of presentation, the structure of the show, the make-up of clothes, and the musical accompaniment of the performance; and (2) the existence of Renteng Dance is the source of the creation of ceremonial dance in Bali because it has a unique appearance that is easy to imitate, according to their aesthetic taste and faith. The new findings of this research show that the level of conflict, aesthetic taste, and faith of the actors greatly influence the development and preservation of the performing arts.